PENGARUH PARTISIPASI MASYARAKAT DAN TEKNOLOGI INFORMASI TERHADAP KINERJA BUM DESA DENGAN INOVASI SEBAGAI VARIABLE INTERVENING - Akhmad Priharjanto; Nina Andriana; Fadlil Usman; Dini Anggraini (Jurnal Sosial Humaniora Sigli, 2022)
The study examined the relationship between community participation and information technology on the performance of village-owned enterprises (BUM Desa) with innovation as an intervening variable. Data was obtained through questionnaires distributed to BUM Desa managers in the East Java region. Questionnaires were distributed online through the East Java Village BUM Forum Whatsapp Group. Filling in the questionnaire was carried out from August to September 2022. The number of respondents who entered was 59 respondents consisting of Directors, Secretaries, Treasurers, and BUM Desa staff. The research model uses the Structural Equation Model - Partial Least Square (SEM PLS). Data processing is used with SMART PLS4. Testing is carried out in two stages, namely testing the outer model and inner model. The results of the study show that community participation and innovation affect the performance of BUM Desa. While information technology does not significantly affect the performance of BUM Desa. However, information technology and community participation jointly affect the performance of BUM Desa through innovation.Keywords: Community Participation, Information Technology, Innovation, Performance, BUM Desa